2021
DOI: 10.1177/2043808720982415
|View full text |Cite
|
Sign up to set email alerts
|

Inducing moral elevation in veterans with PTSD: An experimental investigation using a mixed methods approach

Abstract: Moral elevation is a positive emotion described as feeling inspired by others’ virtuous actions. Elevation has several psychosocial benefits, some of which may be relevant to trauma-related distress; however, past studies have primarily examined elevation in nonclinical, civilian populations or in naturalistic studies. This experimental study used mixed methods to assess if veterans with post-traumatic stress disorder (PTSD) experience elevation when exposed to elevation stimuli in a controlled setting. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…This decision was based on two considerations. First, results from quantitative and qualitative analyses of data from Study 1 indicated the elevation videos elicited a distinct response from positive affect or general amusement that was consistent with the theory of elevation (22); thus, establishing that the same videos used in this study elicit the desired state elevation response within this population. Second, there are significant resource constraints to collecting data for an in-person, experimental study that requires a veteran sample with elevated PTSD symptom severity; thus, a within-person design without a control condition increased feasibility of completing data collection and increased power for the present set of analyses.…”
Section: Participants and Proceduressupporting
confidence: 59%
See 2 more Smart Citations
“…This decision was based on two considerations. First, results from quantitative and qualitative analyses of data from Study 1 indicated the elevation videos elicited a distinct response from positive affect or general amusement that was consistent with the theory of elevation (22); thus, establishing that the same videos used in this study elicit the desired state elevation response within this population. Second, there are significant resource constraints to collecting data for an in-person, experimental study that requires a veteran sample with elevated PTSD symptom severity; thus, a within-person design without a control condition increased feasibility of completing data collection and increased power for the present set of analyses.…”
Section: Participants and Proceduressupporting
confidence: 59%
“…In this pilot study, weekly measures of elevation in response to the acts of fellow group members was associated with greater weekly engagement in the group treatment and lower avoidance symptoms at post-treatment. Notably, results from the initial version of the current experimental study (Study 1) demonstrated that veterans who reported elevated levels of PTSD symptoms can indeed experience elevation in response to portrayals of virtuous behavior (22). In Study 1, veterans reported higher elevation after they watched videos intended to induce elevation compared to a control group that was presented with videos intended to induce general positive affect and amusement.…”
Section: Elevation and Ptsdmentioning
confidence: 74%
See 1 more Smart Citation
“…This study is part of a larger study on the role of positive psychology constructs in the development and maintenance of PTSD; detailed information about the parent study is reported elsewhere (McGuire & Mignogna, 2021). Briefly, the parent study recruited veterans between the ages of 18–90 with subclinical or clinical PTSD symptoms (defined as a positive screen on a symptom checklist, as described below).…”
Section: Methodsmentioning
confidence: 99%
“…However, additional research is needed to further examine the experiences linked with inducing moral elevation in a controlled setting, which may lead to a better understanding of its potential therapeutic effects. This paper aims to extend findings from an experimental study where participants were presented with a trauma reminder and measured for momentary recovery of trauma-related symptoms (McGuire & Mignogna, 2021) by exploring the potential links between induced moral elevation and relevant outcomes among a series of case examples.…”
Section: Introductionmentioning
confidence: 99%